Raindrops roll - Sayre, April Pulley (Beach Lane Books, 2014)
"In her latest gorgeously photo-illustrated nonfiction picture book, celebrated author April Pulley Sayre sheds new light on the wonders of rain, from the beauty of a raindrop balanced on a leaf to the amazing, never-ending water cycle that keeps our planet in perfect ecological balance."--